In‐situ SEM observation of grain growth in the austenitic region of carbon steel using thermal etching - Heard, R; Dragnevski, K; Siviour, C (Wiley, 2020)
A novel heat stage, recently developed for use within the Scanning Electron Microscope, has facilitated Secondary Electron imaging at temperatures up to 850°C. This paper demonstrates one of the applications of in‐situ elevated temperature Scanning Electron Microscope imaging: observation and quantification of grain growth within the austenitic region of carbon steels. The resulting Secondary Electron data have used the technique of thermal etching to capture possible ‘abnormal grain growth’ in the austenitic region. Previous ex‐situ and post‐heating results from carbon steels indicate normal, non‐linear grain growth. Therefore, this new dataset provides greater insight into the heat treatment of steels. From comparison of the in‐situ data with the overall grain growth, measured ex‐situ, it is further concluded that abnormal grain growth is representative of the growth at temperature. Thus, the heating and cooling parts of the heat treatment are likely to account for the non‐linearity previously documented in ex‐situ results and, hence, the range of powers recorded when fitting power law models for steel grain growth. The ability of data derived from in‐situ thermal etching to represent the microstructure of the entire surface and the bulk material is also considered.